Self-assembled lyotropic liquid crystal gel for osteoarthritis treatment via anti-inflammation and cartilage protection. (23rd September 2021) - Mei, Liling; Wang, Hui; Chen, Jintian; Zhang, Ziqian; Li, Feng; Xie, Yecheng; Huang, Ying; Peng, Tingting; Cheng, Guohua; Pan, Xin; Wu, Chuanbin
Abstract : In situ self-assembled lyotropic liquid crystal gel with a spring-like property to buffer joint shock provides highly efficient treatment of osteoarthritis via inflammation alleviation and cartilage protection. Abstract : Osteoarthritis (OA) is a chronic joint disease with occurrence of articular inflammation and cartilage degeneration. An ideal drug delivery system for effective treatment of OA should integrate inflammation alleviation with cartilage protection. Herein, a lyotropic liquid crystal (LLC) precursor co-loading hyaluronic acid (HA) and celecoxib, formulated as the HLC precursor, was developed for the combined therapeutic efficacy. The in situ gelling property of the HLC precursor effectively prolongs drug retention in the articular cavity to achieve a long-term anti-inflammation effect. Based on the rheological tests, HLC gel with a cubic lattice structure endows it with a spring-like effect to buffer joint shock and shows great potential in providing cartilage protection by resisting mechanical destruction, lubricating joint, and decomposing intensive stress (about 50%). Meanwhile, the pharmacodynamics study on the OA-induced SD rats demonstrated that HLC gel was the most effective to reduce inflammation levels and to protect the cartilage against abrasion and degeneration. Furthermore, the in vivo degradation behavior and the intra-articular irritation results of LLC/HLC gel demonstrated that it was biodegradable and biocompatible. These results collectively demonstrated that HLC gel with anti-inflammation and cartilage protection performance provides a useful approach to treat OA.